2015
DOI: 10.1097/md.0000000000001348
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine in Postoperative Analgesia in Patients Undergoing Hysterectomy

Abstract: Both dexmedetomidine and sufentanil modulate spinal analgesia by different mechanisms, and yet no human studies are available on their combination for analgesia during the first 72 hours after abdominal hysterectomy.This CONSORT-prospective, randomized, double-blinded, controlled trial sought to evaluate the safety and efficacy of the combination of dexmedetomidine and sufentanil in intravenous patient-controlled analgesia (PCA) for 72 hours after abdominal hysterectomy.Ninety women undergoing total abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 21 publications
(23 reference statements)
2
45
0
1
Order By: Relevance
“…A multimodal analgesia that could enhance analgesia and reduce the requirement for opioids would be productive. Previous studies conducted by this research group have found that the use of DEX-sufentanil for 72 h after surgery could offer better analgesic effects and patient satisfaction compared with sufentanil alone (Ren et al, 2015a,b). In this study, the dosage of sufentanil was significantly lower in Group D compared with Group ND from 4 to 72 h after surgery ( P < 0.05).…”
Section: Discussionmentioning
confidence: 88%
“…A multimodal analgesia that could enhance analgesia and reduce the requirement for opioids would be productive. Previous studies conducted by this research group have found that the use of DEX-sufentanil for 72 h after surgery could offer better analgesic effects and patient satisfaction compared with sufentanil alone (Ren et al, 2015a,b). In this study, the dosage of sufentanil was significantly lower in Group D compared with Group ND from 4 to 72 h after surgery ( P < 0.05).…”
Section: Discussionmentioning
confidence: 88%
“…Dexmedetomidine (DEX), with its potent and specific affinity of α 2 -adrenergic receptors, [10] has properties of sedation, antianxiety, and analgesic effects, [1115] and can reduce the incidence of POED in pediatric patients undergoing inhalation anesthesia. [11,12,14,1618] However, the impact of DEX on the incidence of POED in pediatric patients after intravenous anesthesia is unknown. In the present study, we observed the safety of intraoperative combination of DEX with intravenous anesthesia in pediatric patients undergoing tonsillectomy with or without adenoidectomy, and validity for the prevention of POED.…”
Section: Introductionmentioning
confidence: 99%
“…[68] A recent study reported that a combination of DEX and sufentani as PCA displayed a significantly improved analgesic effect in patients following hysterectomy. [4] …”
Section: Discussionmentioning
confidence: 99%
“…[49] Accumulating recent evidence is showing that intraoperative DEX with or without a loading dose both reduced morphine consumption, also called morphine-sparing effect, in PCA following general anesthesia. [48] A loading dose is normally administrated within a very short time period, for example, 5 to 10 minutes, which will result in more hemodynamics alterations, such as decrease of blood pressure and heart rate and intraoperative bradycardia. [10] However, the contribution of the loading dose to the proanalgesic effect of morphine-based PCA was largely unknown.…”
Section: Introductionmentioning
confidence: 99%